Biochemical Changes in Blood Serum after Selenium and Zinc Doses and their Effect on the Health and Environment of Kurdi Sheep in Kurdistan Region - Palani, Zirak M. R.; Hamasalim, Hozan Jalil; Abdualmajeed, O. M.; Baqer, Jasim M.; Omer, M. E. A.; Mohammed, Hemin Nuradden; Bchkol, Darwn H. Kak (CV. Literasi Indonesia, 2024)
This study intended to know the effect of sodium selenite and zinc sulfate on the biochemical metabolites in the blood serum of sheep. The experiment was conducted on male sheep of the Kurdi ram and lamb breed in four treatments each as follows; Treatment 1: (control group) without addition, Treatment 2: addition of selenium at a level of 0.5 mg/kg feed, Treatment 3: addition of zinc at a level of 100 mg/kg feed, Treatment 4: addition of selenium with zinc at a level of 0.5 + 100 mg/kg feed for 90 days. The results were significant in the levels of glucose, LDL cholesterol, creatine, immunoglobulin M (IgM), and HDL cholesterol in the second treatment compared to the other treatments and there were no significant differences in the levels of cholesterol and triglycerides in the blood serum. The level of cholesterol increased in the fourth treatment compared to the other treatments in the blood serum, and significant differences were found in the level of albumin and immunoglobulin (IgM) in the fourth treatment compared to the rest of the treatments, and immunoglobulin level (IgG) lowered in all addition treatments compared to the control treatment in the blood serum. We conclude from these results that the addition of selenium and zinc mixture improves some biochemical and immunological properties in the blood serum of rams and lamb of the Kurdi sheep breed.